“Por consiguiente, ha cesado la representación diplomática y consular de la antigua Monarquía de Austria-Hungría” La liquidación de las misiones en Chile (1918-1919) - Martínez-Flener, Milagros (2025)
The new geopolitical order that emerged in Europe in 1919 after the end of World War I was accompanied by the dissolution of the Austro-Hungarian monarchy, the liquidation of all its institutions and the subsequent creation of new ones in accordance with the new Republic of Austria. One of the most complex liquidation processes was that of the Ministry of Foreign Affairs, given that the monarchy had more than five hundred representations around the world and that it was not just a matter of declaring that it had ceased to exist as a political and governmental body. Contemporary documentation stored in the Austrian National Archives makes it possible to take the liquidation of the Austro-Hungarian missions in Argentina, Chile and Peru as an example and to show what it meant to organise the administrative dismantling of these missions, and the feelings of ambiguity faced by the imperial representatives before the Austrian authorities in a period of transition between monarchy and republic.